A K-C3N4@Bi2WO6 photocatalytic material, a rapid synthesis method thereof and applications thereof
By doping and ion exchange of C3N4 and Bi2WO6, K-C3N4@Bi2WO6 multi-level heterogeneous body was constructed, and the existing Bi2WO6 photocatalysts were solved, and efficient photocatalytic degradation and bactericidalization were achieved. Effect.
Patent Information
- Application Number
- CN202210850991.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing Bi2WO6 photocatalysts are difficult to effectively apply in actual engineering due to their low quantum efficiency, low photocatalytic activity, and narrow photoresponse range of monomer materials.
By K-doping the carrier C3N4 and Br doping Bi2WO6, adjusting the reaction pH value to control the size of the Bi2WO6-xBrx composite, achieving spontaneous ion exchange between K-C3N4 and Bi2WO6-xBrx in aqueous solution to generate KBr, and building multi-level heterogeneity Plastid body improves interface binding strength and electron transmission ability.
The photocatalytic degradation rate and bactericidal rate of K-C3N4@Bi2WO6 multi-level heterogeneous bodies have been significantly improved. For example, the degradation rate of tetracycline hydrochloride can be as high as 93%, the bactericidal rate of E. coli is as high as 99.9%, and the material structure and performance are stable. , no significant performance decline after five cycles.
Smart Images

Figure CN117085717B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalytic composite materials, and specifically relates to a KC 3 N 4 @Bi 2 WO 6 Multi-level heterogeneous materials, their controllable construction technology and their applications in sterilization and disinfection, and degradation of organic pollutants. Background Art
[0002] At present, the industrial society is developing rapidly, and the waste pollutants generated in the industrial production process are increasing. These pollutants are mainly organic pollutants. Long-term exposure can easily lead to diseases and cause great damage to the environment. People are gradually aware that the current environmental protection faces many challenges. In addition, the frequent occurrence of SARS, MERS, Ebola, and the new crown pneumonia epidemics have made the general public pay more and more attention to environmental hygiene. The high infectivity, high pathogenicity, and high mortality rate of bacteria and viruses pose a serious threat to human life and health worldwide. Therefore, it is a major challenge to develop a low-cost, easy-to-operate, and pollution-free method to deal with organic pollutants and efficiently sterilize and disinfect. Solar energy is an inexhaustible clean energy. If it can be used to degrade pollutants and have a bactericidal effect at the same time, it will effectively alleviate the current environmental and health problems. Semiconductor photocatalytic technology uses solar energy as the driving force to generate e - and h + It can react with the surrounding oxygen and water to generate active radicals with strong oxidizing properties, which can oxidize and decompose harmful substances in waste pollutants into CO 2 and H 2 O, and can also destroy the DNA and protein of bacteria and viruses to kill bacteria and viruses, and has the advantages of high efficiency, no secondary pollution, and sustainable regeneration. Therefore, it is extremely necessary to study the degradation of pollutants and bactericidal properties of semiconductor photocatalysis.
[0003] The development of photocatalytic technology depends on semiconductor photocatalytic materials. In order to better apply semiconductor photocatalytic materials to the fields of pollutant degradation and sterilization, researchers from all walks of life have developed a variety of new semiconductor photocatalysts, including Bi 2 WO 6 As a bismuth catalyst, it has a faster carrier transfer rate and a suitable bandgap width, can respond to visible light with a wavelength greater than 420nm, and has a high efficiency in utilizing sunlight; it has good stability and can enhance the reuse effect of the catalyst. 2 WO 6 In the field of photocatalysis, it is considered to be a type of catalyst with broad research and application prospects. 2 WO 6Due to the low quantum efficiency, the electrons and holes generated by light excitation are easy to recombine, resulting in low photocatalytic activity. In addition, the narrow visible light response range also restricts its application in practical engineering. Therefore, in the field of photocatalysis, how to expand the light response range of semiconductors and how to improve the catalytic activity of catalysts are currently difficult issues in research. 2 WO 6 Materials modification research, design and preparation of new Bi with excellent photocatalytic performance 2 WO 6 Photocatalytic materials have great research significance in terms of energy conversion and environmental remediation.
[0004] Bi 2 WO 6 Heterostructure construction with other semiconductors is currently considered to be one of the effective methods to achieve photogenerated electron-hole separation and reduce electron-hole recombination. 3 N 4 Due to its advantages of simple preparation method, low cost and adjustable structure, it is also widely used in photocatalytic degradation of pollutants. 3 N 4 with Bi 2 WO 6 The band gap of the two is matched, which makes it easy to form a Z-type heterojunction, and the electrons from C 3 N 4 Transfer to Bi 2 WO 6 On the basis of the built-in electric field formed to improve the separation ability of photogenerated carriers, gC 3 N 4 with Bi 2 WO 6 The strong reduction and oxidation ability of the composite material improves the catalytic degradation ability. However, the current preparation method of this type of composite material often adopts a two-step synthesis method, which is not only complicated, but also has problems such as low interface composite efficiency, low bonding, and difficult electron transmission.
[0005] Therefore, it is necessary to provide a controllable construction technology for heterogeneous composite materials to further improve the interface action mode and bonding strength, enhance the electron transmission capacity, and thus enhance the performance of photocatalytic materials. Summary of the invention
[0006] One of the purposes of the present invention is to overcome the deficiencies of the prior art and provide a KC having excellent degradation and bactericidal properties. 3 N 4 @Bi 2 WO 6 Multi-level heterogeneous composite materials.
[0007] The second object of the present invention is to provide the KC 3 N 4 @Bi 2 WO 6 Ion exchange controllable construction technology of multi-level heterogeneous composite materials:
[0008] First, the vector C 3 N 4 K doping was used to create nitrogen defects, which 2 WO 6 Br doping was performed and the Bi 2 WO 6-x Br x Composite size; then achieve KC during in-situ calcination 3 N 4 with Bi 2 WO 6-x Br x In aqueous solution, ion exchange occurs spontaneously to generate KBr, while KC 3 N 4 The unsaturated C atoms around the upper N defect and Bi 2 WO 6 The surface dangling oxygen bonds form CO bonds, making the interface between the two close to avoid Bi 2 WO 6 They aggregate on their own, improve the efficiency of heterojunction, and provide transmission channels for photogenerated electrons, greatly promoting the separation ability of photogenerated electron-hole pairs.
[0009] Specifically, the present invention provides a KC 3 N 4 @Bi 2 WO 6 Multi-level heterogeneous composite catalytic material: KC 3 N 4 With porous lamellar structure, Bi 2 WO 6 The average particle size of quantum dots is 5-20nm and is evenly loaded on KC 3 N 4 The nitrogen defect sites on the surface of the material are evenly distributed both on the surface and in the pores.
[0010] The present invention also provides the KC 3 N 4 @Bi 2 WO 6 A method for synthesizing a multi-level heterogeneous composite catalytic material comprises the following steps
[0011] (1) Preparation of Bi 2 WO6-x Br x :Take a certain amount of Bi(NO 3 ) 3 ·5H 2 O and Na 2 WO 4 ·2H 2 O is added to ethylene glycol in sequence, and after being evenly dispersed, NaBr is added, and the pH of the mixed solution is adjusted to 4-12, and then transferred to a container for solvent thermal reaction, and then the precipitate is centrifuged, washed, and dried to obtain Bi 2 WO 6-x Br x Powder, the Bi(NO 3 ) 3 ·5H 2 O and Na 2 WO 4 ·2H 2 The molar ratio of O is in the range of 4:1 to 1:2.
[0012] (2) Preparation of KC 3 N 4 Precursor: a certain amount of urea is dissolved in a potassium nitrate solution, the solution is stirred for a certain period of time, vacuum dried, and then ground to obtain a precursor, wherein the mass ratio of urea to potassium nitrate is in the range of 2:1 to 1:1;
[0013] (3) Preparation of KC 3 N 4 @Bi 2 WO 6 Composite material: Bi obtained in step (1) 2 WO 6-x Br x and KC obtained in step (2) 3 N 4 The precursor mixture was dissolved in water and then calcined in a muffle furnace. After cooling to room temperature, the yellow powder was ground to obtain KC 3 N 4 @Bi 2 WO 6 Composite material; KC 3 N 4 Precursor and Bi 2 WO 6-x Br x The molar ratio is 25:1 to 6:1;
[0014] Preferably, in step (1), the temperature of the solvent thermal reaction is 150° C. to 180° C., and the reaction time is 10 h to 18 h.
[0015] Preferably, in step (3), the calcination temperature is 200° C. to 500° C., and the holding time is 0.5 h to 2 h.
[0016] In addition, according to the doping ratio of K to Br and KC 3 N 4 Precursor and Bi 2 WO 6-x Br x The molar ratio of K to Br is calculated to be in the range of 3:1 to 1:1, ensuring that Bi 2 WO 6 All Br in KC 3 N 4 The K ions in the solution are exchanged to form KBr.
[0017] The third purpose of the present invention is to convert KC 3 N 4 @Bi 2 WO 6 Multi-level heterogeneous composite materials are used for sterilization and degradation of organic pollutants.
[0018] The beneficial effects of the present invention are:
[0019] (1) KC prepared by the present invention 3 N 4 @Bi 2 WO 6 The photocatalytic degradation rate of tetracycline hydrochloride (TC) by the multi-level heterogeneous material under visible light irradiation for 30 min can reach 93%, which is comparable to that of C 3 N 4 、Bi 2 WO 6 , C 3 N 4 @Bi 2 WO 6 Compared with the original material, the photocatalytic performance has not decreased significantly after five cycles, and the sterilization rate of Escherichia coli is as high as 99.9%.
[0020] (2) The technology provided by the present invention realizes KC during in-situ calcination 3 N 4 with Bi 2 WO 6-x Br x Spontaneous ion exchange in aqueous solution generates KBr, successfully constructs heterogeneous bodies, improves the interface bonding strength and contact area between the two, improves the heterogeneous bonding efficiency, and thus utilizes KC 3 N 4 and Bi 2 WO 6The strong reducing and oxidizing properties of TC react with the dissolved oxygen and OH- on the catalyst surface to generate active substances with higher oxidizing properties, thus achieving the goal of rapid low-temperature degradation and sterilization of TC.
[0021] (3) KC prepared by this method 3 N 4 @Bi 2 WO 6 Porous heterogeneous composite photocatalytic material, wherein C 3 N 4 K doping is performed to make C 3 N 4 Porous structure, increased specific surface area, up to 52.37m 2 / g, achieving efficient adsorption of TC and E. coli, while creating abundant nitrogen defects on the surface to promote KC 3 N 4 with Bi 2 WO 6 Surface bonding;
[0022] (4) Bi synthesized by pH regulation 2 WO 6-x Br x Microscopic size is small, in KC 3 N 4 The surface of the catalyst is evenly dispersed. Bromine doping can replace some oxygen atoms and improve surface activity. The oxygen defect sites on the surface after Br doping are evenly distributed, which is beneficial to the catalytic reaction as active sites.
[0023] The method provided by the invention has a simple synthesis process and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 KC obtained by the present invention 3 N 4 (KCN) and Bi 2 WO 6-x Br x Synthesis scheme of (BWO-Br).
[0025] Figure 2 The scanning electron microscope (SEM) characterization photos of KCN (Figure b) and BWO-Br (Figure a) obtained in the present invention.
[0026] Figure 3 This is a transmission electron microscope (TEM) characterization photograph of KCN-BWO obtained in Example 1-1 of the present invention.
[0027] Figure 4 The X-ray diffraction (XRD) spectrum of KCN-BWO obtained in the present invention.
[0028] Figure 5 The Fourier transform infrared spectrum (FT-IR) of KCN-BWO obtained in the present invention.
[0029] Figure 6 This is a nitrogen adsorption-desorption curve diagram of KCN-BWO obtained in the present invention.
[0030] Figure 7 This is the X-ray photoelectron spectroscopy (XPS) spectrum of KCN-BWO obtained in the present invention.
[0031] Figure 8 The figure is the UV-visible absorption spectrum of KCN-BWO obtained in the present invention.
[0032] Fig. 9 The figure is the degradation performance diagram of KCN-BWO to TC and the reaction kinetics fitting diagram obtained by the present invention.
[0033] Fig.10 The diagram is a comparison diagram of the degradation performance of tetracycline hydrochloride by KCN-BWO obtained in the present invention and a reaction kinetics fitting diagram.
[0034] Fig.11 The TC performance diagram of KCN-BWO cyclic degradation obtained by the present invention and the XRD spectra before and after use.
[0035] Fig.12 This is a photo of live colonies obtained after the KCN-BWO obtained in the present invention was co-cultured with Escherichia coli for 24 hours.
[0036] Fig.13 The free radical capture experiment and degradation mechanism diagram of KCN-BWO obtained in the present invention, where ·OH - The capture agent is tert-butyl alcohol (TBA), 2 - The capture agent is ascorbic acid (VC), h + The capture agent is triethanolamine (TEOA).
[0037] Fig.14 This is a photocatalytic mechanism diagram of KCN-BWO obtained in the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with specific implementation methods. This embodiment is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential changes and adjustments based on the content of the above invention, which are all within the scope of protection of the present invention.
[0039] The KC prepared by the present invention 3 N4 @Bi 2 WO 6 Multi-level heterogeneity, including C 3 N 4 Compared with alkali metal Na atoms with similar electronic structure, K atoms are inserted into C through the bridging layer. 3 N 4 Between layers, C 3 N 4 The electrons between the layers are localized, expanding the π conjugated system, while Na atoms tend to be doped into the CN plane, increasing the electron density within the plane and hindering the electron transmission in space. 3 N 4 It has strong visible light absorption, carrier separation ability and strong oxidation ability, which is beneficial to improve the degradation of organic pollutants and sterilization ability.
[0040] Example 1
[0041] Example 1-1
[0042] Weigh 600 mg of Bi(NO 3 ) 3 ·5H 2 O and 20mg Na 2 WO 4 ·2H 2 O was added to 60 ml of ethylene glycol, transferred to an ultrasonic cleaner for ultrasonic treatment for 10 min, and then 4 mg of NaBr was added and magnetically stirred for 0.5 h to fully dissolve; NaOH and HNO 3 The pH of the mixed solution was adjusted to 4, and then the mixed solution was loaded into the lining of the reactor for solvent thermal reaction at a reaction temperature of 160° C. for a reaction time of 15 h. Finally, the solution after the reaction was centrifuged, separated, and washed, and the precipitate was vacuum dried for 12 h to obtain BWO-Br.
[0043] Next, weigh 10 g of urea as C 3 N 4 The precursor was dissolved in 25 mL potassium nitrate solution of a certain concentration and stirred for 90 min. The mixed solution was placed in a vacuum dryer at 65 °C and dried for 24 h. The obtained powder was uniformly mixed with a certain amount of BWO-Br in 40 mL of aqueous solution to make KC 3 N 4 :Bi 2 WO 6 The molar ratio is 17:1, and the temperature is raised to 550°C at 5°C / min in a muffle furnace and kept at this temperature for 2 hours; after cooling to room temperature, the yellow powder obtained is further ground to obtain KCN-BWO. The reaction conditions in this embodiment are the optimal conditions.
[0044] Example 1-2
[0045] Compared with Example 1-1, 25 mL of potassium nitrate solution was replaced by 25 mL of sodium nitrate solution, and NaCN-BWO was prepared by further reaction.
[0046] Examples 1-3
[0047] Compared with Example 1-1, 4 mg NaBr was replaced by 4 mg NaF to prepare BWO-F, which was further reacted to prepare KCN-BWO.
[0048] Example 2
[0049] Example 2-1: Compared with Example 1-1, KC 3 N 4 with Bi 2 WO 6 The molar ratio is 38:1.
[0050] Example 2-2: Compared with Example 1-1, KC 3 N 4 with Bi 2 WO 6 The molar ratio is 25:1.
[0051] Example 2-3: Compared with Example 1-1, KC 3 N 4 with Bi 2 WO 6 The molar ratio is 13:1.
[0052] Example 2-4: Compared with Example 1-1, KC 3 N 4 with Bi 2 WO 6 The molar ratio is 6:1.
[0053] The synthesis process of KCN and BWO-Br obtained in Example 1-1 is as follows: Figure 1 As shown, NaBr is first added to the precursor solution of BWO to dope it with bromine. Bromine can replace part of oxygen atoms to improve the surface activity and obtain BWO-Br quantum dots. Then, urea is chemically impregnated for K doping, and the mixture is evenly mixed with BWO-Br in an aqueous solution and then calcined. During the in-situ calcination process, KCN and BWO-Br spontaneously exchange ions in an aqueous solution to generate KBr, successfully constructing a heterogeneous body, and tightly combining them by chemical bonding at surface defects to obtain a KCN-BWO composite material.
[0054] Scanning electron microscopy (SEM) of KCN and BWO-Br obtained according to Example 1-1 Figure 2 As shown, it can be observed that KCN is a porous lamellar structure, BWO-Br is a quantum dot with an average particle size of 5-20 nm, and most of the quantum dots are in an agglomerated state.
[0055] Transmission electron microscopy (TEM) of KCN-BWO obtained according to Example 1-1 Figure 3 As shown in the figure, it can be seen that the morphology of KCN and BWO has not changed significantly. BWO-Br is uniformly loaded on KCN in the form of quantum dots, and no large number of aggregated clusters are formed. Moreover, the BWO quantum dots with obvious lattice fringes are surrounded by amorphous KCN nanosheets. The lattice spacing of d = 0.375nm corresponds to the (111) crystal plane of BWO, indicating that KCN and BWO form a close heterogeneous interface, which is the most direct and effective evidence of the formation of heterojunction. Moreover, the lattice fringes of BWO quantum dots do not show cross-stacking phenomenon, indicating that BWO is dispersed more evenly on amorphous KCN, which can significantly increase the effective interface contact area, thereby improving the catalytic activity.
[0056] X-ray diffraction (XRD) of KCN-BWO obtained according to Example 1-1 Figure 4 As shown in the figure, it can be seen that CN has characteristic peaks corresponding to the (100) crystal plane and the (002) crystal plane at 13.4° and 27.6°, indicating that C 3 N 4 Compared with CN, the (100) crystal plane corresponding to the characteristic peak at 13.4° disappears in KCN, indicating that the successful doping of K atoms has changed the aromatic ring structure in the plane and reduced the C 3 N 4 The electrons between the layers are localized, expanding the π conjugated system. At the same time, the (002) crystal plane corresponding to the characteristic peak at 27.6° widens and shifts toward a lower angle, indicating that the K atom is successfully inserted into the C through the bridging layer. 3 N 4 In addition, in the XRD spectra of the prepared BWO-Br and KCN-BWO, the characteristic peaks at 28.3°, 32.8°, 47.1°, 55.8° and 58.5° correspond to the (131), (200), (331), (262) and (400) crystal planes, respectively, which are consistent with the pure orthorhombic structure Bi 2 WO 6 The characteristic peaks of (JCPDS No.39-0256) are perfectly matched, and KCN-BWO shows KC at 27.6° 3 N 4 The characteristic peaks indicate that the two have been successfully recombined.
[0057] The Fourier transform infrared spectrum (FT-IR) of KCN-BWO obtained according to Example 1-1 Figure 5 As shown, CN and KCN are both at 801 cm -1 1200~1650cm -1 and 3100~3300cm -1 Characteristic absorption peaks appeared at 3 N 4 The bending vibration of the triazine unit in the plane, the bending and stretching vibration of the CN heterocycle and the C 3 N 4 The stretching vibration of the terminal NH bond, while BWO is between 500 and 800 cm -1 The characteristic absorption peaks appearing correspond to the stretching vibrations of Bi-O, WO and WOW bonds, 3100-3300 cm -1 The characteristic absorption peak at 2177 cm is due to adsorbed water or OH. -1 The emergence of new peaks corresponds to the asymmetric stretching vibration of CN, indicating the presence of N defects (N vacancies and C≡N), which is due to the adsorption of OH on the K-doped surface. - With the -NH 2 Dehydration reaction can create an unsaturated coordination environment to participate in surface bonding. After in-situ compounding of KCN and BWO, it can be seen that the KCN-BWO composite material has all the characteristic absorption peaks of KCN, indicating that the loading of BWO has not changed the internal structure of KCN, and the characteristic absorption peaks of BWO can be seen in the KCN-BWO composite material at the same time. The existence of these peaks proves that BWO quantum dots are successfully loaded on KCN and still retain some N defects. In addition, at 989cm -1 The characteristic absorption peak corresponding to the CO bond appears at , indicating that KCN and BWO use ion exchange technology to chemically bond the unsaturated carbon atoms around the N defect with the dangling O on the surface of BWO to form a CO bond, thereby increasing the contact area and bonding strength of the heterogeneous interface, allowing the photogenerated electrons to transfer rapidly in a Z-shaped manner, effectively inhibiting the encounter and recombination of photogenerated electrons and holes, thereby improving the quantum utilization rate, and the structural stability of the material will also be improved.
[0058] The nitrogen adsorption-desorption curve of KCN-BWO was obtained according to Example 1-1. Figure 6As shown, it can be seen that the adsorption amount of KCN is increased by 7.2 times compared with CN, and the specific surface area is also about 3 times that of CN. This is because K doping causes many surface functional groups or unsaturated bonds to exist on the surface of CN, and at the same time, the CN sheets are stacked and peeled off, and larger voids are generated, thereby significantly increasing the specific surface area and pore volume, and the nitrogen adsorption amount increases sharply; while the specific surface area and adsorption amount of pure BWO are very small, only 15% and 4% of KCN respectively. After the formation of KCN-BWO porous heterogeneous body, the specific surface area is four times higher than that of pure BWO, and the adsorption amount is also increased by 5.3 times, which will be conducive to the efficient adsorption of TC and Bacillus.
[0059] The X-ray photoelectron spectroscopy (XPS) spectrum of KCN-BWO obtained according to Example 1-1 Figure 7 As shown, it can be seen that KCN has K 2p at 292.2eV and 294.9eV 3 / 2 and K 2p 1 / 2 The characteristic peaks of C1s and N1s are shifted to the direction of low binding energy compared with CN, which indicates that K atoms are successfully incorporated into CN and interact with the surrounding C and N atoms; BWO-Br has Br 3d corresponding characteristic peaks at 68.34eV and 69.34eV, but not in KCN-BWO, which proves that Br atoms are successfully incorporated into BWO, but exchange with KCN ions to generate KBr during in-situ calcination and remove Br atoms; Bi 4f and W in KCN-BWO Compared with pure BWO, the characteristic peaks of 4f and O1s move toward the low binding energy direction, indicating that the surrounding electron cloud density increases, while the characteristic peaks of C1s and N1s move toward the high binding energy direction compared with KCN, indicating that the surrounding electron cloud density decreases. Combined, after BWO and KCN form a heterojunction, due to the different Fermi level positions of the two, a heterointerface is formed at the contact point. The strong interaction between the two will change the surrounding electron cloud density, and the direction of electron movement is from the electron-rich KCN to BWO. These results show that KCN and BWO form an effective heterojunction. Due to the matching energy band position, the electron cloud density is adjusted, and a built-in electric field is formed at the heterointerface to accelerate electron transfer, thereby improving the separation ability of photogenerated electrons and holes. At the same time, new characteristic peaks appeared in the high-resolution spectra of C1s and O1s in KCN-BWO at 285.9 eV and 532.1 eV, respectively, corresponding to the CO bonds. This indicates that KCN and BWO are connected by CO chemical bonds, which results in a strong chemical reaction between the two, thus improving the interfacial bonding strength of the composite heterogeneity and effectively avoiding the dissolution of the composite heterogeneity during the photocatalytic process, improving the catalytic performance and structural stability, and being more conducive to recycling.
[0060] UV-Vis absorption spectrum of KCN-BWO obtained according to Example 1-1 Figure 8As shown, it can be seen that CN has a strong light absorption ability, and its light absorption edge is around 450nm. After 450nm, the absorption of light is almost zero. The (αhν) obtained by conversion of the formula 1 / 2 The relationship diagram with photon energy shows that the band gap of CN is 2.71eV. Although the light absorption intensity in the range of 200-450nm has decreased after K doping, the absorption edge has red-shifted and the band gap has narrowed to 2.15eV, which can effectively improve the absorption and utilization of visible light; in addition, it can be seen from the figure that BWO-Br also has a certain absorption capacity for light in the range of 400-800nm, with a band gap of 2.63eV; and KCN-BWO has enhanced light absorption capacity compared with KCN, and a narrower band gap than CN, which expands the visible light absorption range, so KCN-BWO has the best light absorption capacity, which is beneficial to the photocatalytic reaction.
[0061] Degradation performance diagram of KCN-BWO to TC and reaction kinetics fitting obtained according to Example 1-1 Fig. 9 As shown in the figure, it can be seen that the degradation rate of tetracycline hydrochloride by pure CN can only reach about 40% after 30 minutes of illumination, and the degradation performance decreases after K doping. This is because its band gap is reduced and the conduction band position moves up, which makes the valence band position move up, and the oxidation ability is reduced; pure BWO has a strong oxidation ability due to its positive valence band position, but it has a high electron-hole recombination rate, so the degradation rate of tetracycline hydrochloride by 30 minutes of illumination can only reach 48%. After KCN and BWO are combined to form a composite heterogeneous body, the degradation rate of tetracycline hydrochloride reaches the highest, that is, 93% of tetracycline hydrochloride can be degraded in 30 minutes, which is comparable to C 3 N 4 、Bi 2 WO 6 , C 3 N 4 @Bi 2 WO 6 The results showed that the reaction rate was 53%, 45% and 16% higher than that of the control group, and the reaction rate was as high as 0.03min. -1 , which are 2.2 and 1.9 times the degradation rates of pure CN and BWO, respectively, indicating that the degradation of TC is more advantageous in terms of reaction kinetics, and the complete mineralization of TC can be achieved in a relatively short time. However, CN-BWO can only degrade 77% of tetracycline hydrochloride within 30 minutes, and its degradation performance is slightly worse than that of KCN-BWO. This is because KCN has the advantages of large specific surface area, high porosity, and strong reducing ability. After in-situ compounding with BWO, the built-in electric field improves the electron transfer ability and carrier separation efficiency, so the catalytic degradation performance reaches the best.
[0062] Degradation performance comparison diagram of tetracycline hydrochloride obtained from KCN-BWO according to Examples 1-1, 2-1, 2-2, 2-3, and 2-4 and reaction kinetics fitting Fig.10 As shown, the corresponding icons of Examples 1-1, 2-1, 2-2, 2-3, and 2-4 are KCN-BWO, KCN-BWO-1, KCN-BWO-2, KCN-BWO-3, and KCN-BWO-4, respectively. It can be found that with the increase of BWO content, the degradation rate and reaction rate of KCN-BWO gradually increase. When KCN:BWO=17:1, the highest degradation performance reaction rate is achieved, that is, 93% of tetracycline hydrochloride is degraded within 30 minutes, and the reaction rate is as high as 0.03min -1 ; When the BWO content continues to increase, its photocatalytic degradation performance and reaction rate decrease instead. This is because the appropriate composite ratio can, on the one hand, give play to the advantages of KCN's large specific surface area and porosity to improve its adsorption capacity for tetracycline, and on the other hand, it can form an effective heterogeneous body to improve the carrier separation ability, ultimately improving the catalytic activity; but when the ratio of KCN to BWO exceeds 17:1, the BWO quantum dots will aggregate and agglomerate into particles deposited on the catalyst surface, resulting in a reduction in active sites and effective heterogeneous interfaces, leading to a corresponding decrease in its catalytic activity.
[0063] TC performance diagram of KCN-BWO cycle degradation obtained according to Example 1-1 and XRD spectra before and after use Fig.11 As shown, it can be seen that after 5 cycles of use, the crystal structure of KCN-BWO has not changed significantly and still maintains a high catalytic activity. However, due to the loss of KCN-BWO multi-level heterogeneity during the centrifugal recovery process and the attachment of intermediates to the catalyst surface, the adsorption capacity of tetracycline hydrochloride will be reduced to a certain extent, so the degradation performance is slightly reduced.
[0064] Photo of live colonies obtained after co-culturing KCN-BWO obtained in Example 1-1 with Escherichia coli for 24 hours Fig.12 It can be seen that the bactericidal rate of KCN-BWO composite material is much higher than that of pure CN and BWO, reaching 99.9.9%, achieving complete bactericidal and antibacterial effect; while the bactericidal rates of pure CN and BWO calculated according to the proportion of viable colony count can only reach 24% and 46%, respectively, which cannot achieve complete sterilization.
[0065] Free radical capture experiment and degradation mechanism of KCN-BWO obtained according to Example 1-1 Fig.13 As shown in the figure, it can be seen that after adding the ·OH- scavenger TBA, the catalytic performance of the KCN-BWO multi-level heterogeneous material is minimally affected, and the degradation rate is only 6% lower than that without the additive, indicating that ·OH - The contribution to the entire photocatalytic degradation process is minimal; while the addition of ·O2 - The capture agents VC and h + After adding the capture agent TEOA, the ability of KCN-BWO to degrade tetracycline hydrochloride decreased significantly, indicating that during the catalytic degradation process, 2 - and h + It is the main active group in the catalytic reaction.
[0066] Photocatalytic mechanism of KCN-BWO obtained according to Example 1-1 Fig.14 As shown in the figure, combined with the free radical capture experiment, the catalytic mechanism is as follows: 0D BWO quantum dots are evenly dispersed on the surface and pores of 2D KCN to form a KCN-BWO multi-level heterogeneous structure, in which KCN, due to its large specific surface area and pore size distribution, firstly achieves efficient adsorption of TC and E. coli; secondly, C 3 N 4 After K doping and loading BWO, the visible light absorption range is expanded and the utilization rate of visible light is improved. More photogenerated electrons and holes can be generated under light. Under the action of the built-in electric field formed by the contact between BWO and KCN, the photogenerated electrons and holes excited by the two are transferred through the surface chemical bond CO in a Z-type system. That is, most of the photogenerated electrons gather on the KCN conduction band and react with the surrounding adsorbed oxygen to produce more oxidizing ·O 2 - Most of the photogenerated holes are concentrated in the BWO valence band, some of which directly oxidize TC and E. coli cell membranes, and some of which react with the surrounding OH - The reaction produces OH - These free radicals further oxidatively degrade the adsorbed TC and bacteria. The successful construction of the Z-type heteromer achieves the effective spatial separation of photogenerated electrons and holes, and retains the strong reducing and oxidizing abilities of both, thereby increasing the number of active groups involved in catalytic degradation, thereby achieving rapid oxidation of tetracycline hydrochloride and Escherichia coli adsorbed on the surface.
[0067] According to the light degradation experiment of tetracycline hydrochloride by NaCN-BWO obtained in Example 1-2, the degradation rate in 30 minutes was only 56%, which was lower than that of CN-BWO, indicating that Na doping is not conducive to the degradation of organic pollutants because Na atoms tend to be doped into the CN plane, increasing the electron density in the plane, which is not conducive to the transmission of electrons in space, thereby reducing the catalytic efficiency.
[0068] According to the light degradation experiment of tetracycline hydrochloride by KCN-BWO obtained in Example 1-3, the degradation rate in 30 minutes was only 44%, indicating that the quantum dot Bi 2 WO 6 F doping does not contribute to the 2 WO6 With KC 3 N 4 Surface bonding.
Claims
1. A method for synthesizing a K-C3N4@Bi2WO6 multi-level heterogeneous composite catalytic material, wherein the K-C3N4 has a porous lamellar structure, the Bi2WO6 is a quantum dot with an average particle size of 5-20 nm and is uniformly loaded on the surface and pores of the K-C3N4, and the nitrogen defect sites on the surface of the material are uniformly distributed; characterized in that: The following steps are involved: (1) Preparation of Bi2WO 6-x Br x : Take a certain amount of Bi(NO3)3·5H2O and Na2WO4·2H2O and add them to ethylene glycol in sequence. After uniform dispersion, continue to add NaBr and adjust the pH of the mixed solution to 4-12. Then transfer it to a container for solvothermal reaction. Then centrifuge, wash and dry the precipitate to obtain Bi2WO 6-x Br x Powder, the molar ratio of Bi(NO3)3·5H2O to Na2WO4·2H2O is in the range of 4:1 to 1:2, and the molar ratio of Bi(NO3)3·5H2O to NaBr is in the range of 20:3 to 10:1; (2) preparing a K-C3N4 precursor: taking a certain amount of urea and dissolving it in a potassium nitrate solution, continuously stirring and vacuum drying it, and then grinding it to obtain a precursor, wherein the mass ratio of urea to potassium nitrate is in the range of 2:1 to 1:1; (3) Preparation of K-C3N4@Bi2WO6 composite material: The Bi2WO6 obtained in step (1) 6-x Br x The K-C3N4 precursor obtained in step (2) is mixed and dissolved in water, and then placed in a muffle furnace for calcination. After cooling to room temperature, the yellow powder obtained is ground to obtain a K-C3N4@Bi2WO6 composite material; the K-C3N4 precursor and Bi2WO 6-x Br x The molar ratio is 25:1 to 6:
1.
2. The synthesis method according to claim 1, characterized in that In step (1), the temperature of the solvent thermal reaction is 150° C. to 180° C., and the reaction time is 10 h to 18 h.
3. The synthesis method according to claim 1, characterized in that In step (3), the calcination temperature is 200° C. to 500° C., and the insulation time is 0.5 h to 2 h.
Citation Information
Patent Citations
Potassium-doped carbon nitride composite bismuth oxybromide photocatalysis material and preparation method thereof
CN110743600A
Preparation method of high-photocatalysis phosphorus-doped graphite phase carbon nitride / bismuth tungstate heterojunction
CN114130415A